New data on African Cheloninae (Hymenoptera, Braconidae) show a strong biogeographic signal for taxa with spined propodea - Braet, Yves; Rousse, Pascal; Sharkey, Michael (Zootaxa, 2012)
Eight species of Cheloninae (Hymenoptera, Braconidae) are newly described: Ascogaster kibalensis Braet sp. nov., Chelonus(Chelonus) mayi Braet & Rousse sp. nov., Chelonus (Microchelonus) madagasakarensis Braet & Rousse sp. nov., Chelonus(Microchelonus) matilei Braet & Rousse sp. nov. Chelonus (Microchelonus) merdicus Rousse & Braet sp. nov., Odontospha-eropyx gracilis Braet sp. nov., O. leucocoxus Braet sp. nov., and Phanerotomella erena Braet sp. nov. They are all from theMalagasy subregion and several of them share the presence of spine-like apophyses on the propodeum. This character is cate-gorized for future phylogenetic use. The genus Pachychelonus Brues, 1924 is recognized as junior synonym of the genus Odon-tosphaeropyx Cameron, 1910. Three new combinations are proposed Odontosphaeropyx maximus (Zettel, 2002) comb. nov., O.fulviventris (Brues, 1924) comb. nov. and O. flavifasciatus (Zettel, 1990a) comb. nov. for Pachychelonus maximus Zettel, 2002,P. fulviventris Brues, 1924 and P. flavifasciatus Zettel, 1990a, respectively. Updated keys of species Phanerotomella and Odontosphaeropyx are provided. New distribution data about Cheloninae from Africa are also given.